Research on Multi-Agent Modeling Method of Space Based Network Information System. Issue 1 (August 2021) - Lai, Jiazhe; Yu, Haoze; Zhang, Zhening
Abstract: Space based information network system is a network system composed of spacecraft and spacecraft, which plays an immeasurable role in commercial and military, so it is very important to carry out simulation research on it. In this paper, the idea of Multi-Agent modeling is applied to study the simulation modeling of space-based network information system. This paper first introduces the space-based network information architecture, Multi-Agent system and RepastHPC, a Multi-Agent high-performance computing simulation toolbox. The simulation example is Starlink's information support capability under AIM-260 "A aims and directs B to strike" fire attack mode, and the process of message Starlink transmission is mainly studied. In this paper, the space-based network information system is abstracted into route agent and sat agent, the decision-making method is given for each behavior, and a feasible Multi-Agent system is established. The simulation experiment of information transmission is carried out on RepastHPC platform, and the feasibility of applying Multi-Agent system to space-based network information system is verified.